1976
DOI: 10.1021/bi00650a017
|View full text |Cite
|
Sign up to set email alerts
|

Electrofocusing and kinetic studies of adult and embryonic chicken pyruvate kinases

Abstract: Chicken embryos less than 15 days old contain only the K isozyme of pyruvate kinase, which appears to exist in vivo as an R,T conformational set with pI values of 7.2 and 6.6, respectively. Sets of lower pI and higher pI K-isozyme variants also are obtained. Whole embryos of 15 days or more of development show progressively increasing amounts of higher pI, lower K0.5S enzymatic variants. Tissue distribution and kinetic properties suggest that the highest pI form (pH 8.8-9.0) is an M-isozyme analogue. The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…This latter conclusion is supported by isoelectrozymograms using pH 6-9 gradients that show that this band can be resolved into three under the proper conditions (data not shown). Such multiple bands between the K4-and M4-bands have also been observed by others (Ibsen et al, 1976, Guguen-Guillouzo et al, 1977Cottreau et al, 1982). Extracts of adult spleen yield a single peak with a PI value of 6.8, suggesting this variant is the K4-isozyme.…”
Section: Differentiation Of Pyruvate Kinase In Cultured Astrocytessupporting
confidence: 81%
See 1 more Smart Citation
“…This latter conclusion is supported by isoelectrozymograms using pH 6-9 gradients that show that this band can be resolved into three under the proper conditions (data not shown). Such multiple bands between the K4-and M4-bands have also been observed by others (Ibsen et al, 1976, Guguen-Guillouzo et al, 1977Cottreau et al, 1982). Extracts of adult spleen yield a single peak with a PI value of 6.8, suggesting this variant is the K4-isozyme.…”
Section: Differentiation Of Pyruvate Kinase In Cultured Astrocytessupporting
confidence: 81%
“…Whether these low PI forms represent differences in covalent structure or in conformation is not clear. That similar low PI variants can be derived from the K4-isozyme (Ibsen and Trippet, 1972;Ibsen et al 1975Ibsen et al , 1976 suggests they may be conformational variants. In any case, that they are preferentially expressed in less differentiated cells suggests they have physiological significance.…”
Section: Pyruvate Kinase Isozyme Expression In Differentiating Astrocmentioning
confidence: 90%
“…Further additions to the classical pyruvate kinase isoenzymes have been observed in developing and regenerating liver. Hybrid forms have been reported in vitro (Dyson & Cardenas, 1973;Saheki et al, 1978) and occur naturally in bovine (Strandholm et al, 1976), chicken (Ibsen et al, 1976;Cardenas et al, 1978) and guinea-pig tissues (Whittell et al, 1973). Although it has been suggested that PKl is synthesized in the parenchymal cells, whereas PK4 is produced in the Kupffer cells (van Berkel etal., 1972), culturedhepatocytes from regenerating liver have been shown to shift from synthesizing PK1 to PK4 (Garnett et al, 1974), indicating the potential ofcells to produce both isoenzymes, and this is supported by the existence of hybrid forms.…”
Section: Discussionmentioning
confidence: 99%